GENDER LANGUAGE CHARACTERISTICS USED BY STUDENTS IN SCHOOL - Chrystin Wulandary Sipahutar; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study deals with the gender language characteristics used by students in school. The objectives of this study were to reveal the gender language characteristics used by students and to describe why students interact using the gender language characteristics in school. The research design in this study was a descriptive qualitative. The data was collected by observing language utterances between male and female students from one class of grade eight and interview. The findings of this study show that sometimes male students used female language characteristics, and female students also used male language characteristics in school. And the male students used 6 kinds of female language characteristics, and the female students used 9 kinds of male language characteristics. The most dominant female language characteristic used by female students is taq questions, while the most dominant male language characteristic used by male students is minimal responses. And, there are four reasons that affect the use of language characteristics used by female and male students in school, namely equal status, formal situation, positive affect, and contact. So, the researcher can conclude that the female students are more dominant in using female and male language characteristics in school. In addition, of the four reasons that affect students' use of language characteristics, frequent contact is the dominant reason affecting students' use of language characteristics when they communicate